Controlling w banku spółdzielczym - założenia i cele - Ostojski, Wojciech (Controllership in a Co-Operative Bank - Foundations and Purposes, 2006)
The article presents the theoretical consideration in respect of possibilities of the use of controllership in a co-operative bank. It discusses foundations and purposes of controllership and considers controllers, their roles and tasks in a co-operative bank. The proper identification of "bottlenecks" in the co-operative bank's activity allows for more efficient resources management and it maximizes the shareholders wealth.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 304-309